Genetic parameters for temperament and facial hair whorl traits in Canchim cattle - de Oliveira Bessa, Ayrton Fernandes; Genuíno, Maria Victória Henrique; dos Santos Câmara, Giovanna Maria [UNESP]; Teixeira, Roney [UNESP]; Bugner, Ana Luisa Paçó; Maffei, Walsiara Estanislau; Ribeiro, Andrea Roberto Bueno; Souza, Vanessa Aparecida Feijó; Marcondes, Cintia Righetti; Buzanskas, Marcos Eli [UNESP] (Elsevier, 2025)
The growing demand for improved animal welfare has increased interest in the genetic evaluation of temperament traits and related indicators, such as facial hair whorls, in beef cattle. This study aimed to estimate genetic parameters for temperament scores (movement, tension, breathing, vocalization, reactivity, and flight time) and facial hair whorl traits in the composite Canchim breed. Phenotypic data from 2145 animals born between 2013 and 2022 were provided by Embrapa Pecuária Sudeste (São Carlos, SP, Brazil), including 375 males and 1770 females. Temperament was assessed at four different ages, whereas hair whorls were recorded once. Fixed effects of sex, month-year at birth, order-period of entry of batch in the evaluation, lineage, and age at measurement were evaluated and considered in the contemporary groups when relevant. Hair whorls were classified according to their horizontal position (absent, left, middle, and right) and vertical location (absent, low, mid, and high), and additional traits such as number, height, and presence/absence of whorls were recorded. Genetic parameters were estimated using Bayesian threshold-linear animal models, with repeatability estimated for temperament traits. Heritability estimates for temperament traits ranged from 0.09 to 0.35, with repeatabilities from 0.16 to 0.55. For whorl traits, heritability estimates ranged from 0.18 to 0.57. These findings demonstrate that both temperament and hair whorl traits exhibit sufficient additive genetic variability. Genetic correlations among temperament traits ranged from −0.78 to 0.99, among whorl traits from 0.32 to 1.00, and between temperament and whorl traits from 0.49 to 0.87. It can highlight the existence of interesting genetic correlations between movement with the whorls in the left, middle, low, and mid positions, as well as with the whorl’s height (ranging from 0.72 to 0.87). Favorable genetic correlations were observed between reactivity with whorls in the left, middle, and low positions, as well as with the whorl's height and absence/presence of facial whorls. Facial hair whorls represent a practical and heritable indicator for the early selection of animals with favorable temperaments, offering an opportunity to optimize phenotyping and achieve indirect genetic gains, especially for movement and reactivity.